High-temperature-resistant polymer PASA as well as preparation method and application thereof

The high-temperature resistant polymer PASA prepared by copolymerization solves the problems of reduced strength and short glue formation time under high temperature conditions, and achieves high stability and sealing effect of leak plugging agent at high temperature.

CN119390908APending Publication Date: 2025-02-07CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411747837.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The strength of acrylamide gels decreases under high temperature conditions, which can easily lead to failure of leak plugging operations, and the glue formation time is short, making it easy to have "enema".

Method used

PASA, a high temperature resistant polymer made of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, allyl alkylphenol polyoxyethylene ether and N-acryloylmorpholine copolymer, is used to adjust the monomer concentration , initiator concentration and synthesis temperature to prepare a leak plugging agent with high elastic modulus and stability.

Benefits of technology

Improve the temperature resistance and stability of the leak plugging agent under high temperature conditions, extend the glue forming time, enhance the sealing rate, and realize the controllable glue forming time by adjusting the ratio of retarder and crosslinking agent. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390908A_ABST
    Figure CN119390908A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil-gas field development, and provides a high-temperature-resistant polymer PASA (Polyacrylonitrile-Acrylic Acid) as well as a preparation method and application of the high-temperature-resistant polymer PASA. The high-temperature-resistant polymer PASA contains an acrylamide (AM) structural unit, a 2-acrylamide-2-methylpropanesulfonic acid (AMPS) structural unit, an allyl alkylphenol polyoxyethylene ether (SMA) structural unit and an N-acryloylmorpholine (ACMO) structural unit, and the plugging agent prepared from the high-temperature-resistant polymer PASA is good in high-temperature resistance, high in flowability, easier to pump underground and underground, controllable in gelling time, good in plugging performance and suitable for being used as a plugging agent for plugging of a well. And after aging for a period of time, excellent plugging performance is still realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oil and gas field development, and in particular to a high temperature resistant polymer PASA and a preparation method and application thereof. Background Art

[0002] Acrylamide materials are fully mixed with additives before being pumped into the wellbore. Under the action of formation temperature, they can be cross-linked to form a chemical colloid with a spatial network structure and viscoelasticity. Before the acrylamide material is gelled, it is a low-viscosity fluid and is easy to be pumped into the wellbore. Under the dual action of additives and formation temperature, the viscosity gradually increases, forming a gel plug in the wellbore, and it has a certain pressure-bearing performance, which can play the role of bearing pressure, consolidating the formation and repairing the wellbore wall in the fractured formation. Acrylamide gel has good chemical stability, and has the advantages of wide source of raw materials, low price, good corrosion resistance, strong comprehensive water absorption performance, and not easy to deform under pressure. Adding suitable cross-linking agents and additives can effectively adjust the gel performance and effectively meet the construction requirements. However, when the temperature rises, the properties of the functional groups on the gel polymer chain will change, the ends of the molecular chains will shrink and curl, and the strength of the gel plugging agent will gradually decrease, and even the connection between the cross-linking agent and the polymer will break, resulting in a decrease in the cross-linking density of the gel plugging agent, a larger three-dimensional network structure space, and ultimately the gel plugging agent. Ineffective. In addition, under high temperature conditions, the gelling time is short and "enema" phenomenon is prone to occur, resulting in the plugging operation not being able to proceed smoothly.

[0003] The Chinese invention patent with patent number CN202111352266.9 provides a heat-resistant and salt-resistant multi-polymer thickener and a preparation method thereof. Acrylamide (AM), sodium 2-acrylamido-2-methylpropyl sulfonate (AMPS), vinyl pyrrolidone (NVP), and acryloylmorpholine (ACMO) are mixed evenly in a certain proportion, and an appropriate amount of redox initiator and a water-soluble azo initiator are added. The mixture is stirred and reacted under a constant temperature and anaerobic conditions of 60-90°C. After solvent sedimentation, cooling and consolidation, natural drying, and then shearing and crushing, a heat-resistant and salt-resistant multi-polymer thickener is obtained. The heat-resistant and salt-resistant multi-polymer thickener has the advantages of good salt resistance, hydrolysis resistance, heat resistance, and shear resistance.

[0004] Although the above technology solves the technical problem that acrylamide materials are not resistant to high temperatures, its finished product is a thickener and cannot achieve the technical purpose of using it as a plugging agent in this application. Therefore, it is not applicable to the technical problems and applicable conditions raised in this application and has certain disadvantages. Summary of the invention

[0005] The purpose of the present application is to provide a high temperature resistant polymer PASA, which is copolymerized by acrylamide (AM), 2-acrylamide-2-methylpropane sulfonic acid (AMPS), allyl alkylphenol polyoxyethylene ether (SMA) and N-acryloylmorpholine (ACMO), and has the characteristics of high temperature resistance and high stability.

[0006] Another object of the present application is to provide a method for preparing the high temperature resistant polymer PASA.

[0007] Another object of the present application is to provide a plugging agent, the raw material of which includes high temperature resistant polymer PASA.

[0008] In order to solve the above technical problems, the technical solution adopted in this application is:

[0009] On the one hand, the embodiment of the present application provides a high temperature resistant polymer PASA, whose chemical structure is shown in Formula 1:

[0010] In Formula 1, x=74.5%-97.9%, y=1%-15%, z=0.1%-0.5%, m=1%-10%, the weight average molecular weight of the high temperature resistant polymer PASA is 480,000, and the viscosity average molecular weight is 950,000.

[0011] Figure 1 This is a synthetic route for the above-mentioned high temperature resistant polymer PASA, wherein x (acrylamide structural unit) is 74.5%-97.9%, y (2-acrylamide-2-methylpropanesulfonic acid structural unit) is 1%-15%, z (allyl alkylphenol polyoxyethylene ether structural unit) is 0.1%-0.5%, and m (acryloyl morpholine structural unit) is 1%-10%.

[0012] Polyacrylamide itself can be used as a thickener for gel plugging agent, but the gel plugging agent prepared by polyacrylamide gel has poor heat resistance and viscoelastic properties, and its structural unit contains amide groups, which are easy to form hydrogen bonds, making it have good water solubility and high chemical activity, and it is easy to obtain a variety of modified products with branched or mesh structures by grafting or cross-linking, so this application selects acrylamide monomer as the synthetic main chain, 2-acrylamide-2-methylpropane sulfonic acid (AMPS) contains polymerizable vinyl and hydrophilic sulfonic acid groups, which can be copolymerized with a variety of water-soluble and non-water-soluble monomers, and the sulfonic acid group has certain heat resistance; N-acryloyl morpholine (ACMO) is a functional monomer and active diluent with excellent performance, with double bonds and morpholine groups, so the chemical properties are relatively active, and it has the characteristics of low viscosity, fast curing, strong dilution ability, etc. Allyl alkylphenol polyoxyethylene ether (SMA) contains benzene rings, which can enhance the rigidity and stability of the molecule and enhance the heat resistance of the polymer. Therefore, AM, AMPS, ACMO and SMA are selected as synthetic raw materials.

[0013] On the other hand, an embodiment of the present application provides a method for preparing the above-mentioned high temperature resistant polymer PASA, comprising the following steps: mixing acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, allyl alkylphenol polyoxyethylene ether and N-acryloylmorpholine in a molar ratio of 8.5:0.2-1:0.1:0.4-1.2 to obtain a monomer, adding water to form a solution with a molar concentration of 8%-12%, and adding an initiator with a molar concentration of 0.3%-0.5% to initiate copolymerization to obtain a high temperature resistant polymer PASA.

[0014] In the preparation method of the above-mentioned high temperature resistant polymer PASA, the method specifically includes the following steps: S1, acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, allyl alkylphenol polyoxyethylene ether and N-acryloylmorpholine in a molar ratio of 8.5:0.2-1:0.1:0.4-1.2 are mixed to obtain a monomer, and then water is added to prepare a solution A with a molar concentration of 8%-12%, S2, an initiator is taken, and water is added to prepare an initiator solution with a molar concentration of 0.3%-0.5%; the mass of the initiator is 3% of the mass of the monomer, S3, nitrogen is introduced into solution A for deoxygenation for 15 minutes, heated to 30-70°C in a water bath, stirring is started and nitrogen is continuously introduced, S4, the initiator solution is dripped into solution A, and the dripping time is controlled to be 15 minutes, S5, stirring and polymerizing for 3 hours, and cooling to obtain a high temperature resistant polymer PASA.

[0015] The concentration of the monomer affects the elastic modulus of the gel. When it is lower than 8%, the concentration is low, there are fewer collisions with the initiator in the reaction vessel, and the reaction is slow, resulting in a shorter polymer chain length, which is manifested as low strength on a macro scale. When the monomer concentration increases, the polymerization reaction accelerates, and the product chain length increases, thereby increasing the gel strength. When the monomer concentration exceeds the critical value, the polymer reaction rate will be too fast, resulting in implosion, thereby synthesizing a large amount of low molecular weight products, and the gel strength decreases after cross-linking. Therefore, the monomer concentration is selected to be 8%-12%.

[0016] When the initiator concentration is low, the efficiency of initiator decomposition will be reduced, resulting in fewer free radicals, a slow chain initiation reaction, limited chain length, a low polymerization rate, a longer reaction time, and a larger polymer molecular weight, so the gel strength will increase. As the initiator concentration increases, the number of free radicals increases accordingly. In the polymerization stage, there are not enough monomers to react with free radicals, which will also cause monomer free radicals and macromolecular chain free radicals to transfer to the initiator and lose their activity to terminate the reaction. The resulting polymer molecular chain is shorter, resulting in reduced gel strength. Therefore, the initiator concentration is selected to be 0.3%-0.5%.

[0017] As the temperature increases, the elastic modulus of the gel increases first and then decreases. When the temperature is low, the free radicals of the initiator split are less and the speed is slow. Until the end of the reaction, some monomers still do not participate in the reaction, so the polymer chain length is short and the molecular weight is low, so the strength of the cross-linked gel is low. As the temperature rises, the concentration of free radicals from the initiator cleavage increases, and the polymer chain length increases accordingly, and finally the macroscopic gel strength increases. When the temperature is too high, the initiator splits too fast, the reaction is too violent, and chain transfer and chain termination are prone to occur, which ultimately reduces the degree of polymerization and the molecular weight, resulting in a decrease in gel strength. Therefore, the heating temperature is selected to be 30℃-70℃.

[0018] In some embodiments of the present application, the initiator is a persulfate, and the persulfate includes one or more of ammonium persulfate, potassium persulfate and sodium persulfate.

[0019] The embodiment of the present application also provides a plugging agent, the raw material of which includes the above-mentioned high temperature resistant polymer PASA.

[0020] In some embodiments of the present application, the plugging agent comprises the following components, measured in molar concentration: 2%-8% of high temperature resistant polymer PASA, 0.2%-2% of cross-linking agent, 6%-10% of retarder and the balance of water.

[0021] As the concentration of the heat-resistant polymer PASA increases, the elastic modulus value of the gel increases rapidly. When it reaches the peak value, the growth rate of the elastic modulus value of the gel slows down when the polymer concentration continues to increase, and the incremental concentration of the heat-resistant polymer PASA contributes less to the strength of the gel. This is because the heat-resistant polymer PASA is used as a thickener. The higher the concentration, the denser the cross-linking points between the macromolecular chain and the cross-linking agent, and the smaller the three-dimensional network space formed, so the gel strength will increase; when the concentration is too high, the cross-linking density between the polymer and the cross-linking agent will decrease, and the excess polymer molecular chains will exist in a free state. Although the strength still increases, the increase is very small, and the initial viscosity will also increase significantly. Therefore, the concentration of the heat-resistant polymer PASA is selected to be 2%-8%.

[0022] After the high temperature resistant polymer PASA is cross-linked, when the cross-linking agent reaches a certain concentration, the change in gel strength after gelation decreases. When the cross-linking agent is too low, the polymer does not gel. When the concentration is too high, the gel strength no longer increases. Therefore, the cross-linking agent concentration is selected to be 0.2%-2%.

[0023] After adding the retarder, when the concentration of the retarder is low, the thickening time of the gel remains basically unchanged, indicating that the low concentration of the retarder has no significant retarding effect on the gel at high temperature. When the concentration reaches a certain value, the retarding time increases rapidly until it reaches the peak value, and the trend gradually slows down. When the retarder concentration is increased later, the change rate of the gelation time decreases, and the gelation time benefit decreases. Therefore, the retarder concentration is selected to be 6%-10%.

[0024] In some embodiments of the present application, the cross-linking agent includes one or more of zirconium trichloride, potassium chromium sulfate, potassium dichromate, basic chromium acetate, aluminum trichloride, aluminum sulfate and copper sulfate.

[0025] In some embodiments of the present application, the retarder includes one or more of acetate, lactate, citrate, phosphate, metaphosphate, and amino acid salt.

[0026] In some embodiments of the present application, the plugging agent is prepared by the following method: dissolving a high temperature resistant polymer PASA, a cross-linking agent and a retarder in water to prepare the plugging agent.

[0027] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0028] 1. The high temperature resistant polymer PASA has low viscosity before cross-linking, so the pressure is low when pumped into the formation and the probability of retention in the wellbore is low.

[0029] 2. The high temperature resistant polymer PASA has a high elastic modulus, so it has high strength and better crack sealing performance.

[0030] 3. The plugging agent made of high temperature resistant polymer PASA has good high temperature resistance, high stability and high plugging rate when used underground.

[0031] 4. The plugging agent made of high temperature resistant polymer PASA still has high strength after aging for a certain period of time under high temperature conditions, and the higher the temperature, the shorter the gelling time.

[0032] 5. The plugging agent made of high temperature resistant polymer PASA can achieve a controllable gelation time within the range of 1.5-4.5h by adjusting the ratio of retarder to cross-linking agent.

[0033] 6. The plugging agent made from high temperature resistant polymer PASA has good compatibility and a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 A schematic diagram of a synthesis route of a high temperature resistant polymer PASA provided by the present invention;

[0036] Figure 2 A bar graph showing the viscoelastic changes in monomer concentration in Example 1 of a high temperature resistant polymer PASA provided by the present invention;

[0037] Figure 3 A bar graph showing the viscoelastic changes in initiator concentration in Example 2 of a high temperature resistant polymer PASA provided by the present invention;

[0038] Figure 4 A bar graph showing the viscoelastic changes at synthesis temperature in Example 3 of a high temperature resistant polymer PASA provided by the present invention;

[0039] Figure 5 A bar graph showing the change in the viscoelasticity of the monomer molar ratio in Example 5 of a high temperature resistant polymer PASA provided by the present invention;

[0040] Figure 6 This is a relative molecular mass distribution diagram of Example 7 of a high temperature resistant polymer PASA provided by the present invention;

[0041] Figure 7 This is a test diagram of elastic modulus of high temperature resistant polymer PASA of different concentrations in Example 8 of a plugging agent provided by the present invention;

[0042] Figure 8 This is a concentration optimization trend diagram of different concentrations of high temperature resistant polymer PASA in Example 8 of a plugging agent provided by the present invention;

[0043] Fig. 9 This is a test diagram of elastic modulus of cross-linking agents of different concentrations in Example 9 of a plugging agent provided by the present invention;

[0044] Fig.10 A preferred trend diagram of the concentration of cross-linking agents of different concentrations in Example 9 of a plugging agent provided by the present invention;

[0045] Fig.11 The test graph and trend graph of different concentrations of retarders in Example 10 of a plugging agent provided by the present invention;

[0046] Fig.12This is a scanning electron microscope result diagram of test example 1 of a plugging agent provided by the present invention;

[0047] Fig.13 This is a test result diagram of the normal temperature rheological properties, variable temperature rheological properties and viscosity at different shear rates in Test Example 2 of a plugging agent provided by the present invention;

[0048] Fig.14 This is a graph showing the results of the temperature resistance test at 150°C and 160°C in Test Example 3 of a plugging agent provided by the present invention;

[0049] Fig.15 Schematic diagram of a plugging performance testing device in Test Example 4 of a plugging agent provided by the present invention. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0051] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0052] A high temperature resistant polymer PASA comprises the following steps:

[0053] S1, mixing acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, allyl alkylphenol polyoxyethylene ether and N-acryloylmorpholine in a molar ratio of 8.5:0.2-1:0.1:0.4-1.2 to obtain a monomer, and then adding water to prepare a solution A with a molar concentration of 8%-12%;

[0054] S2. Take the initiator and add water to prepare an initiator solution with a molar concentration of 0.3%-0.5%; the mass of the initiator is 3% of the mass of the monomer;

[0055] S3, nitrogen was introduced into solution A for deoxygenation for 15 min, and the solution was heated to 50-70°C in a water bath, and stirring was started while nitrogen was continuously introduced;

[0056] S4, dripping the initiator solution into solution A, controlling the dripping time to be 15 min;

[0057] S5, stirring and polymerizing for 3 hours, and obtaining a high temperature resistant polymer PASA after cooling.

[0058] A plugging agent comprises the following steps:

[0059] The plugging agent is prepared by dissolving 2%-8% of the high temperature resistant polymer PASA, 0.2%-2% of the cross-linking agent and 6%-10% of the retarder in water.

[0060] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0061] Example 1

[0062] This embodiment 1 provides a high temperature resistant polymer PASA, and the preparation process includes the following steps:

[0063] S1, acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, allyl alkylphenol polyoxyethylene ether and N-acryloylmorpholine in a molar ratio of 8.5:0.2:0.1:1.2 are mixed to obtain a monomer, and water is added to prepare a solution A with a molar concentration of 8%;

[0064] S2, taking ammonium persulfate as an initiator, adding water to prepare an initiator solution with a molar concentration of 0.3%; the mass of the initiator is 3% of the mass of the monomer;

[0065] S3, nitrogen was introduced into solution A for deoxygenation for 15 min, and the solution was heated to 50°C in a water bath, and stirring was started while nitrogen was continuously introduced;

[0066] S4, dripping the initiator solution into solution A, controlling the dripping time to be 15 min;

[0067] S5, stirring and polymerizing for 3 hours, and obtaining a high temperature resistant polymer PASA after cooling.

[0068] In order to achieve the best effect of synthesizing the high temperature resistant polymer PASA, the concentration of the monomer is optimized, and therefore control experimental groups 1-4 are also set up, which are basically the same as the steps of Example 1, except that the monomer concentrations of the control experimental groups 1-4 are set to 9%, 10%, 11% and 12%, respectively.

[0069] After polymerization, the viscoelasticity test was performed on Example 1 and control experimental groups 1-4. The viscoelasticity test conditions were fixed at 30°C, 1 Hz frequency, and 10 Pa stress. In order to more clearly observe the strength change law, the average value of the viscoelasticity test results was taken to draw a viscoelasticity change bar graph, as shown in FIG. Figure 2 As shown, from Figure 2 It can be seen that as the monomer concentration increases, the elastic modulus of the gel first remains stable, reaches 171Pa, and then drops sharply to 102Pa. The gel strength reaches the maximum when the monomer concentration is 9%, so the optimal monomer concentration is 9%.

[0070] Example 2

[0071] This embodiment 2 is basically the same as embodiment 1, except that the monomer concentration is set to 9%.

[0072] In order to achieve the best effect of synthesizing the high temperature resistant polymer PASA, the concentration of the initiator is optimized, and therefore control experimental groups 5-8 are also set up, which are basically the same as the steps of Example 2, except that the initiator concentrations of the control experimental groups 5-8 are set to 0.35%, 0.4%, 0.45% and 0.5%, respectively.

[0073] After polymerization, the viscoelasticity test was performed on Example 2 and control experimental groups 5-8. The viscoelasticity test conditions were fixed at 30°C, 1 Hz frequency, and 10 Pa stress. In order to more clearly observe the strength change law, the average value of the viscoelasticity test results was taken to draw a viscoelasticity change bar graph, as shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that with the increase of initiator concentration, the elastic modulus of the gel first increases and then decreases. When the initiator concentration reaches 0.35%, the strength of the gel reaches the maximum, which is 300 Pa. Therefore, the initiator concentration of 0.35% is optimal.

[0074] Example 3

[0075] This embodiment 3 is substantially the same as embodiment 2, except that the initiator concentration is set to 0.35%.

[0076] In order to achieve the best effect of synthesizing the high temperature resistant polymer PASA, the synthesis temperature is optimized, and therefore control experimental groups 9-12 are also set up, which are basically consistent with the steps of Example 3, except that the synthesis temperatures of the control experimental groups 9-12 are set to 55°C, 60°C, 65°C and 70°C, respectively.

[0077] After polymerization, the viscoelasticity test was performed on Example 3 and control experimental groups 9-12. The viscoelasticity test conditions were fixed at 30°C, 1 Hz frequency, and 10 Pa stress. In order to more clearly observe the strength change law, the average value of the viscoelasticity test results was taken to draw a viscoelasticity change bar graph, as shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that with the increase of experimental temperature, the elastic modulus of the gel first increases and then decreases. When the synthesis temperature reaches 65°C, the strength of the gel reaches the maximum, which is 300Pa. Therefore, the synthesis temperature is optimal at 65°C.

[0078] Example 4

[0079] This embodiment 4 is basically the same as embodiment 3, except that the synthesis temperature is set to 30°C.

[0080] The optimal temperature for synthesizing the high temperature resistant polymer PASA was tested in Example 3. The purpose of this Example 4 is to test whether polymerization is possible at 30°C. Consistent with the test steps of Example 3, after the viscoelastic test, it was found that the elastic modulus of the gel began to increase at 30°C, indicating that polymerization began at 30°C. Therefore, the lowest synthesis temperature is 30°C.

[0081] Example 5

[0082] This embodiment 5 is basically the same as embodiment 3, except that the synthesis temperature is set to 65°C.

[0083] In order to achieve the best effect of synthesizing the high temperature resistant polymer PASA, the monomer molar ratio is optimized. Therefore, control experimental groups 13-16 are also set up, which are basically the same as the steps of Example 5, except that the monomer molar ratios of AM:AMPS:SMA:ACMO in the control experimental groups 13-16 are set to 8.5:1:0.1:0.4, 8.5:0.8:0.1:0.6, 8.5:0.6:0.1:0.8 and 8.5:0.4:0.1:1, respectively.

[0084] After polymerization, the viscoelasticity test was performed on Example 5 and the control experimental groups 13-16. The viscoelasticity test conditions were fixed at 30°C, 1Hz frequency, and 10Pa stress. In order to more clearly observe the strength change law, the average value of the viscoelasticity test results was taken to draw a viscoelasticity change bar graph, as shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that as the monomer molar ratio changes, the elastic modulus is relatively stable and changes little. When the monomer molar ratio is 8.5:0.8:0.1:0.6, the elastic modulus reaches a maximum of 325 Pa, so the preferred monomer molar ratio is AM:AMPS:SMA:ACMO=8.5:0.8:0.1:0.6.

[0085] Example 6

[0086] This Example 6 is basically the same as Example 5, except that the molar ratio of monomers is set to AM:AMPS:SMA:ACMO=8.5:0.8:0.1:0.6.

[0087] Based on Examples 1-5, it is concluded that the factors affecting the synthesis results of the high temperature resistant polymer PASA are mainly monomer concentration, initiator concentration, synthesis temperature and monomer molar ratio. In order to obtain the optimal value under the comprehensive conditions, the four factors are marked as A, B, C, and D (Table 1), and 9 groups of orthogonal experiments are designed according to these four influencing factors, which are marked as control experimental groups 17-24, respectively. The steps are basically the same as those in Example 6, except that different monomer concentrations, initiator concentrations, synthesis temperatures and monomer molar ratios are set.

[0088] In addition to considering the strength factor, the wellbore fluidity of the high temperature resistant polymer PASA gel must also be considered. Therefore, the initial viscosity before gelation is specially added as an evaluation criterion in the orthogonal experiment. The orthogonal test factors are shown in Table 1, and the orthogonal test scheme is shown in Table 2.

[0089] Table 1 Orthogonal test factor levels

[0090]

[0091] Table 2 Orthogonal experimental design

[0092]

[0093]

[0094] According to the above design, a total of 9 groups of experiments were conducted to measure the viscosity μ of the polymer at room temperature before gelation, and the viscoelastic properties after gelation at 150°C. The experimental formula was 6.4% high temperature resistant polymer PASA + 1.6% cross-linking agent, and the cross-linking agent was potassium chromium sulfate. For plugging gel, the lower the viscosity before gelation, the better the fluidity in the wellbore, the less likely it is to be blocked in the wellbore, and the higher the utilization rate of the gel. Its viscoelasticity characterizes the dynamic modulus of the gel, including G' elastic modulus and G” viscous modulus. The elastic modulus represents the energy stored in the deformation process of the polymer gel, and the viscous modulus represents the energy lost in the deformation and flow process of the polymer. For polymer plugging gel, the larger the elastic modulus, the higher its strength, indicating that its crack plugging performance is better. The results of the orthogonal experiment are shown in Table 3. In order to better evaluate the comprehensive performance of the polymer, the viscosity and elastic modulus are standardized, recorded as X and Y respectively, and then the two evaluation indicators are given the same weight. H is a comprehensive evaluation index, recorded as H=YX. The larger H is, the lower the gel viscosity, the higher the strength, and the better the plugging effect. Among the four factors, the monomer molar ratio has the greatest impact on the comprehensive effect of synthesizing polymer PASA, followed by monomer concentration, temperature and initiator concentration. From the mean results, it can be concluded that the optimal synthesis conditions are A1, B1, C3, and D3, that is, monomer concentration 8% + initiator 0.3% + synthesis temperature 70°C, and the monomer molar ratio is AM:AMPS:SMA:ACMO=8.5:0.9:0.1:0.5.

[0095] Table 3

[0096]

[0097]

[0098] Example 7

[0099] This Example 7 is basically the same as Example 6, except that the monomer concentration is 8%, the initiator concentration is 0.3%, the synthesis temperature is 70° C., and the monomer molar ratio is AM:AMPS:SMA:ACMO=8.5:0.9:0.1:0.5.

[0100] In order to detect the weight average molecular weight and viscosity average molecular weight of the high temperature resistant polymer PASA, the high temperature resistant polymer PASA synthesized by Example 7 was subjected to gel permeation chromatography (GPC) detection. The GPC test results are as follows: Figure 6 As shown in the figure, the blue line represents the relative molecular mass differential distribution curve, and the red line represents the cumulative mass distribution curve. As can be seen from the figure, the relative molecular mass of the product is mainly distributed between 50,000 and 1 million, and its cumulative mass exceeds 70%, among which the relative molecular mass between 100,000 and 300,000 accounts for the highest proportion. As shown in Table 4-8, the weight average molecular weight of PASA is about 480,000, the viscosity average molecular weight is about 950,000, and the PDI (Mn / M W ) is 1.98, indicating that the molecular weight distribution is relatively wide. From the experimental results, it can be seen that small molecular weight polymers occupy the main body of the product. The viscosity of the gel solution prepared in this way is relatively low. When pumping on site, the pumping pressure is low and it will not be retained in the wellbore. The test results are shown in Table 4.

[0101] Table 4

[0102]

[0103] Example 8

[0104] On the basis of Example 7, this Example 8 is a plugging agent composed of the high temperature resistant polymer PASA synthesized in Example 7, a cross-linking agent and a retarder, and the specific steps are as follows:

[0105] A plugging agent is prepared by dissolving 2% of a high temperature resistant polymer PASA, 1.5% of potassium chromium sulfate and 4% of sodium citrate in water.

[0106] In order to optimize the concentration of the high temperature resistant polymer PASA in the plugging agent, control experimental groups 25-30 were also set up, which were basically the same as Example 8, except that the concentrations of the high temperature resistant polymer PASA were set to 3%, 4%, 5%, 6%, 7% and 8%, respectively.

[0107] The elastic modulus was tested using a HAAKE rheometer. The specific experimental results are as follows: Figure 7 As shown, when the experimental conditions remain unchanged, the test results of each gel are relatively stable, indicating that the mechanical properties of the gel are relatively stable, which is conducive to the gel sealing of formation cracks.

[0108] In order to more clearly show the change law of elastic modulus, the viscoelastic test results of each concentration were averaged and a trend graph was drawn ( Figure 8 ), as the polymer concentration increases from 2% to 6%, the elastic modulus value of the gel rises rapidly. When the polymer concentration reaches 6%, the growth rate of the elastic modulus value of the gel slows down as the polymer concentration continues to increase, and the contribution of the polymer concentration increment to the strength of the gel becomes smaller. This is because the higher the concentration of the high temperature resistant polymer PASA as a thickener, the denser the cross-linking points between the macromolecular chain and the cross-linking agent, and the smaller the three-dimensional network space formed, so the gel strength will increase; when the concentration is too high, the cross-linking density between the polymer and the cross-linking agent will decrease, and the excess polymer molecular chains will exist in a free state. Although the strength still increases, the increase is very small, and the initial viscosity will also increase significantly. Therefore, the concentration of the high temperature resistant polymer PASA is selected to be 6%.

[0109] Example 9

[0110] This Example 9 is basically the same as Example 8, except that the concentration of the high temperature resistant polymer PASA is 6%.

[0111] In order to optimize the concentration of the cross-linking agent in the plugging agent, control experimental groups 31-36 were also set up, which were basically the same as Example 8, except that the concentration of potassium chromium sulfate was set to 0.1%, 0.3%, 0.5%, 0.8%, 1%, and 2%, respectively.

[0112] The elastic modulus was tested using a HAAKE rheometer. The specific experimental results are as follows: Fig. 9 shown.

[0113] After the polymer is cross-linked, the elastic modulus of the gel is relatively stable. When the cross-linking agent reaches a certain concentration, the change in gel strength after gelation decreases. In order to more significantly show the change of gel strength with the concentration of the cross-linking agent, the average value of the elastic modulus is taken and the change curve is drawn ( Fig.10 ). When the cross-linking agent concentration is 0.1%, the polymer does not gel. When the cross-linking agent concentration reaches 1%, the gel strength no longer increases. Therefore, the concentration of the cross-linking agent potassium chromium sulfate is selected to be 1%.

[0114] Example 10

[0115] This Example 10 is substantially the same as Example 9, except that the concentration of potassium chromium sulfate is 1%.

[0116] In order to optimize the concentration of the retarder in the plugging agent, control experimental groups 38-42 were also set up, which were basically the same as Example 10, except that the concentrations of sodium citrate were set to 5%, 6%, 7%, 8%, 9% and 10%, respectively.

[0117] The prepared plugging agents were placed in high-temperature and high-pressure thickeners for thickening experiments. Considering the actual situation on site and the properties of the polymer itself, the experimental conditions were set at 150°C and 60MPa, and then the changes in the gelling time of the gel were observed.

[0118] The experimental results show that when the retarder concentration is 4%, the gelation time is 102 minutes. When the cross-linking conditions are met, the retarder will quickly decompose and release the cross-linking agent. When the cross-linking agent contacts the polymer PASA, it will quickly cross-link to form a high-strength gel. The curing time is about 5 minutes, and the initial consistency is about 6BC ( Fig.11 When the retarder concentration is 5%, the gelling time is 105min, and the gelling time increases. When the cross-linking conditions are reached, the curing time is about 5min, and the initial consistency is about 6BC ( Fig.11 When the retarder concentration is 6%, the gelling time is 120min, which increases by 15min. When the cross-linking condition is reached, the curing time is about 5min, and the initial consistency is about 6BC ( Fig.11 When the retarder concentration is 7%, the gelling time is 160min, which increases by 40min. When the cross-linking condition is reached, the curing time is about 5min, and the initial consistency is about 6BC ( Fig.11 When the retarder concentration is 8%, the gelling time is 160min, which increases by 85min. When the cross-linking condition is reached, the curing time is about 5min, and the initial consistency is reduced to about 4BC ( Fig.11 When the retarder concentration is 9%, the gelation time is 260min, the gelation time increases by 15min, and the increase rate begins to slow down. When the cross-linking conditions are reached, the curing time is about 5min, and the initial consistency increases to about 12BC ( Fig.11 When the retarder concentration is 10%, the gelation time is 270min, the gelation time increases by 10min, and the increase rate is further reduced. When the cross-linking conditions are reached, the curing time is about 5min, and the initial consistency returns to about 6BC ( Fig.11 ).

[0119] Before the gel solution is gelled, the solution has a low viscosity, generally within 10BC, indicating that the solution has good fluidity in the wellbore and will not thicken due to temperature rise, which is more beneficial for on-site pumping. When the thickening conditions are reached, the gel solution solidifies rapidly, and the solidification time is within 10 minutes. When the gel solution stays in the formation for too long, the gel solution is easily diluted by the formation water, resulting in low formation plugging efficiency and other problems, so rapid solidification is beneficial to formation plugging. In order to more clearly observe the relationship between gelation time and retarder concentration, a relationship diagram between gelation time and retarder concentration was drawn ( Fig.11), when the retarder concentration is low, the thickening time of the gel remains basically unchanged, indicating that the low concentration retarder has no significant retarding effect on the gel at high temperature. When the concentration reaches 6%, the retarding time increases rapidly until the concentration reaches 8%, the trend gradually slows down, and when the retarder concentration is increased in the later period, the rate of change of the gelation time decreases, and the benefit of the gelation time decreases. When the retarder concentration is 8%, the benefit reaches the maximum. Overall, under 150°C conditions, the gelation time of the gel can be adjusted by controlling the concentration of the retarder, and the time change is controllable and controllable between 1.5 and 4.5 hours. The formula of the plugging agent is determined as follows: 6% high temperature resistant polymer PASA + 1% potassium chromium sulfate + 8% sodium citrate.

[0120] Test Example 1

[0121] The purpose of this test example 1 is to detect the structure of the plugging agent. On the basis of Examples 7-9, a plugging agent was prepared with a formula of 6% high temperature resistant polymer PASA + 1% potassium chromium sulfate + 8% sodium citrate. The cross-linked plugging agent was dried at 60°C, and small pieces with regular shapes were taken out for scanning electron microscopy testing. The experimental results are as follows: Fig.12 shown.

[0122] from Fig.12 It can be seen that the trunk structure and branch structure are clearly distributed, and the network structure is densely interwoven. The gaps in each unit grid are small and dense, showing a regular distribution. The trunk part is almost a macromolecular structure. The closer to the trunk, the denser the fibrous structure is, and the better the interweaving state. Similarly, the branch part is also a macromolecular structure aggregation area. The entire gel network structure is supported by the trunk and branch structures, and small molecular chain structures are crossed during the period, eventually forming a stable network structure.

[0123] From the figure, we can see that the network structure is uneven. We can infer that the entire gel body is a three-dimensional network structure composed of multiple network surfaces. Fig.12 (b) This can be confirmed by the fact that the linear molecular chain structure is interwoven up and down, presenting a multi-layer structure, each layer of which is Fig.12 (a) shows a tree-like network structure, with layers connected by filamentous network structures. This shows that the gel plugging agent is a three-dimensional grid structure formed by interweaving multiple layers of tree-like network structures.

[0124] Test Example 2

[0125] The purpose of this test example 2 is to detect the rheological properties of the plugging agent. On the basis of Examples 7-9, a plugging agent is prepared with a formula of 6% high-temperature resistant polymer PASA + 1% potassium chromium sulfate + 8% sodium citrate. 50 mL is taken out and the rheological properties are tested using a HAAKE MARSⅢ rheometer. The tests are carried out at room temperature (30°C) and variable temperature (20-150°C), respectively. The conditions are set as a shear rate of 170s-1 and a shear time of 120min. The rheological properties of the gel solution under high-speed shear conditions are observed. The configured plugging agent can flow like clear water, indicating that it has good fluidity.

[0126] The results of the room temperature rheological test are as follows Fig.13 As shown in the figure, at 30°C, the viscosity of the gel solution is very stable, remaining at about 48 mPa·s. This simulates the ground transportation conditions of the gel solution. The experiment shows that the gel solution with lower viscosity is conducive to pipeline transportation.

[0127] The variable temperature rheological test simulates the pumping process from the ground to the target layer. The experimental results are as follows: Fig.13 As shown, as the temperature rises, the viscosity of the gel solution decreases, but the decrease is low, and the viscosity decreases by only about 10 mPa·s, indicating that in this process, the molecular structure of each chemical component in the gel system is not destroyed.

[0128] The viscosity of the gel solution changes under different shear rates. Fig.13 As shown in the figure, with the change of shear rate, the viscosity is stable at about 50mPa·s, which means that the viscosity of the gel will not be diluted due to shear, and the gel solution will flow easily in the wellbore. After reaching the formation, it will not be diluted due to shear, so it can stay in the formation cracks as much as possible, greatly improving the plugging efficiency.

[0129] Test Example 3

[0130] The purpose of this test example 3 is to test the temperature resistance of the plugging agent. On the basis of Examples 7-9, a plugging agent is prepared with a formula of 6% high-temperature resistant polymer PASA + 1% potassium chromium sulfate + 8% sodium citrate. At 150°C and 160°C, the prepared plugging agent is divided into 12 portions and placed in a high-temperature reactor respectively. After high-temperature cross-linking for 1 hour, one portion is taken out to measure its viscoelasticity, and then one portion is taken out at 1h, 2h, 3h, 5h, 12h, 24h, 48h, 72h, 96h, 120h, 144h, and 168h to measure its viscoelasticity.

[0131] At 150℃, the strength of the gel is relatively stable and remains basically unchanged for 48 hours, indicating that the gel plugging system can normally plug cracks at 150℃. At 150℃, the three-dimensional grid structure of the gel plugging agent is not destroyed. Since it is in a closed environment, water molecules do not evaporate, so the strength of the gel remains stable and still maintains good plugging performance after aging for 7 days. Fig.14 .

[0132] Under 160℃, the gel strength decreased in the first 24 hours, but the decrease was not large. However, after 48 hours, the gel strength decreased by 40%, indicating that the gel plugging material has limited temperature resistance at 160℃ and cannot plug the formation for a long time. This is because, under 160℃, the polymer chain ends of the gel plugging agent curl and shrink, and some uncrosslinked unstable polymer molecular structures with small chain lengths are destroyed, so the initial strength decreases. When the unstable structure is destroyed, the gel still maintains a certain strength in the later stage, such as Fig.14 .

[0133] Fig.14 Shown is a schematic diagram of the initial state of the plugging agent in the pipeline at 150°C and 160°C and the state after aging for 7 days.

[0134] The above tests show that the plugging agent can stably plug the formation at 150°C and can short-term plug the formation at 160°C.

[0135] Test Example 4

[0136] The purpose of this test example 4 is to test the plugging performance of the plugging agent. On the basis of Examples 7-9, a plugging agent is prepared with a formula of 6% high temperature resistant polymer PASA + 1% potassium chromium sulfate + 8% sodium citrate. The experiment is carried out using a sand filling pipe plugging method. The experimental device is as follows: Fig.15 As shown, the specific steps are as follows:

[0137] 1) Take 40-60 and 20-40 mesh quartz sand, fill two sand filling tubes respectively, and compact them appropriately;

[0138] 2) In order to simulate the formation conditions, standard brine was prepared to simulate the formation water. The standard brine formula is: 2.0% KCl + 5.5% NaCl + 0.45% MgCl 2 +0.55% CaCl 2 ;

[0139] 3) Use standard brine to measure the leakage rate K of the sand-filled pipe 1 , ×10 -3 μm 2 ;

[0140] 4) Displacing the gel solution into the sand-filled tube until the flow rate at the outlet is stable, indicating that the gel solution in the sand-filled tube has reached saturation;

[0141] 5) Heat the sand-filled pipe to 80°C using a heating device until the plugging agent is completely cross-linked;

[0142] 6) After the sand-filled tube has cooled, use standard brine to measure the permeability K of the sand-filled tube again. 2 , ×10 -3 μm 2 ;

[0143] 7) The plugging rate of the sand filling pipe is calculated according to formula 4-1:

[0144]

[0145] In order to ensure the accuracy of the experiment, different mesh sizes of quartz sand were used to fill the sand filling tube. The experimental results are shown in Table 5. The plugging efficiency of the gel plugging agent for 40-60 mesh quartz sand is 97.35%, and the permeability after plugging is 0.241×10 -3 μm 2 The plugging efficiency of 20-40 mesh quartz sand is 97.005%, and the permeability after plugging is 0.512×10 -3 μm 2 This experiment is to determine the efficiency of gel plugging agent in plugging drilling fluid, but drilling fluid is easy to be blocked in the pipeline, so the liquid used in this experiment is simulated formation water. The experimental results show that the gel solution has a good plugging effect on formation water, from which it can be inferred that the permeability of drilling fluid with a higher solid content will be lower after gel plugging.

[0146] Table 5

[0147]

[0148] Test Example 5

[0149] The purpose of this test example 5 is to test the pressure bearing capacity of the plugging agent. The pressure bearing capacity is an important criterion for evaluating the performance of the plugging agent. On the basis of Examples 7-9, a plugging agent is prepared with a formula of 6% high temperature resistant polymer PASA + 1% potassium chromium sulfate + 8% sodium citrate. In order to test the pressure bearing capacity of the plugging agent, rock samples with different seam widths are used respectively, and the seam widths are set to: 0.05mm, 0.1mm, 0.2mm, 0.5mm, 1.0mm, 2.0mm and 5mm. The pressure bearing capacity of the gel plugging agent under different seam width conditions is determined according to the experimental results. The experimental conditions are 120℃, 0.5-10MPa, and the applicable equipment is a core plugging evaluation instrument.

[0150] The experimental data are shown in Table 6. As the pressure increases, the rock sample with a fracture width of 0.05 mm has no leakage throughout the whole process. The rock sample with a fracture width of 0.1 mm begins to leak when the pressure reaches 10 MPa, with a total leakage of 0.13 mL. The rock sample with a fracture width of 0.2 mm begins to leak at 7 MPa, but the leakage is only 0.041 mL, which can be ignored. At 10 MPa, the leakage is 0.512 mL. The rock sample with a fracture width of 0.5 mm begins to leak at 7 MPa, and the leakage increases from 0.108 mL to 2.428 mL at 10 MPa. The rock samples with a fracture width of 1 mm and 2 mm begin to leak at a pressure of 6 MPa, and the cumulative leakage is the largest, reaching 9.655 mL and 8.766 mL, respectively. The rock sample with a fracture width of 5 mm begins to leak at 5 MPa, and the cumulative leakage is 11 mL at 9 MPa. From the results of the pressure bearing capacity test, it can be seen that the pressure bearing capacity of the gel plugging agent is different when sealing cracks of different widths. When the width of the crack is less than 0.1mm, the pressure bearing capacity reaches more than 9MPa. When the width of the crack is less than 2mm, the pressure bearing capacity is 6-7MPa. When the width of the crack is 5mm, the pressure bearing capacity is 4MPa.

[0151] Table 6

[0152]

[0153] After the plugging agent is gelled, there is a viscous force between it and the crack wall. When the pressure applied by the drilling fluid to the gel is lower than the viscous force between the gel and the crack wall, the gel can completely seal the crack. The viscous force between the gel and the crack wall is related to the roughness of the crack wall and the gel performance. The higher the roughness of the crack wall, the greater the viscous force and the better the sealing performance; the denser the network structure of the gel itself, the greater the contact with the crack wall, and then the greater the viscous force. In addition to the upstream pressure, the pressure applied by the drilling fluid to the gel is related to the crack width. The larger the crack width, the greater the pressure on the gel, and the more difficult it is for the gel to seal the crack. As the crack width increases, the greater the pressure applied by the drilling fluid to the gel, but the viscous force between the gel and the crack wall remains unchanged, so the pressure bearing capacity of the gel becomes lower and lower. When the crack width is 5mm, the pressure bearing capacity drops to 4MPa.

[0154] In summary, the high temperature resistant polymer PASA and the plugging agent composed of the high temperature resistant polymer PASA of the embodiments of the present invention have the following advantages: the high temperature resistant polymer PASA has low viscosity before cross-linking, so the pressure is low when pumped into the formation and the probability of retention in the wellbore is low; the high temperature resistant polymer PASA has a high elastic modulus, so the strength is high and the crack plugging performance is better; the plugging agent made of the high temperature resistant polymer PASA has good high temperature resistance, high stability and high plugging rate when underground; the plugging agent made of the high temperature resistant polymer PASA still has high strength after aging for a certain period of time under high temperature conditions, and the higher the temperature, the faster the gelation time; the plugging agent made of the high temperature resistant polymer PASA can achieve a controllable cross-linking time within the range of 1.5-4.5h by adjusting the ratio of the retarder to the cross-linking agent; the plugging agent made of the high temperature resistant polymer PASA has good compatibility and a wide range of applications.

[0155] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A high temperature resistant polymer PASA, characterized in that: The chemical structure of the high temperature resistant polymer PASA is shown in Formula 1: In Formula 1, x=74.5%-97.9%, y=1%-15%, z=0.1%-0.5%, m=1%-10%, and the weight average molecular weight of the high temperature resistant polymer PASA is 480,000, and the viscosity average molecular weight is 950,000.

2. A method for preparing the high temperature resistant polymer PASA according to claim 1, characterized in that: The following steps are involved: Acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, allyl alkylphenol polyoxyethylene ether and N-acryloylmorpholine in a molar ratio of 8.5:0.2-1:0.1:0.4-1.2 are mixed to obtain a monomer, water is added to prepare a solution with a molar concentration of 8%-12%, and an initiator with a molar concentration of 0.3%-0.5% is added to initiate copolymerization to obtain the high temperature resistant polymer PASA.

3. The method for preparing the high temperature resistant polymer PASA according to claim 2, characterized in that: The following steps are involved: S1, mixing acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, allyl alkylphenol polyoxyethylene ether and N-acryloylmorpholine in a molar ratio of 8.5:0.2-1:0.1:0.4-1.2 to obtain a monomer, and then adding water to prepare a solution A with a molar concentration of 8%-12%; S2, take an initiator, add water to prepare an initiator solution with a molar concentration of 0.3%-0.5%; the mass of the initiator is 3% of the mass of the monomer; S3, nitrogen was introduced into the solution A for deoxygenation for 15 min, and the solution was heated to 30-70° C. in a water bath, and stirring was started while nitrogen was continuously introduced; S4, dripping the initiator solution into the solution A, controlling the dripping time to be 15 min; S5, stirring and polymerizing for 3 hours, and obtaining the high temperature resistant polymer PASA after cooling.

4. The method for preparing the high temperature resistant polymer PASA according to claim 3, characterized in that: The initiator is a persulfate, and the persulfate includes one or more of ammonium persulfate, potassium persulfate and sodium persulfate.

5. A plugging agent, characterized in that: The raw material of the plugging agent includes the high temperature resistant polymer PASA described in claim 1.

6. The plugging agent according to claim 5, characterized in that: In terms of molar concentration, the raw materials of the plugging agent include the following components: High temperature resistant polymer PASA 2%-8%, cross-linking agent 0.2%-2%, retarder 6%-10% and the balance water.

7. The plugging agent according to claim 6, characterized in that: The cross-linking agent includes one or more of zirconium trichloride, potassium chromium sulfate, potassium dichromate, basic chromium acetate, aluminum trichloride, aluminum sulfate and copper sulfate.

8. The plugging agent according to claim 6, characterized in that: The retarder includes one or more of acetate, lactate, citrate, phosphate, metaphosphate, and amino acid salt.

9. The plugging agent according to any one of claims 6 to 8, characterized in that: The plugging agent is prepared by the following method: The high temperature resistant polymer PASA, a cross-linking agent and a retarder are dissolved in water to prepare a plugging agent.

Citation Information

Patent Citations

  • Temperature-resistant and salt-resistant multi-component polymerization thickening agent and preparation method thereof

    CN113788911A